Sir Reader Bullard, Frank Roberts and the Azerbaijan crisis of 1945–46: Bevin's officials, perceptions and the adoption of a Cold War mentality in British Soviet Policy. Issue 3 (3rd July 2017) - Shaw, Alexander Nicholas
Abstract: This article evaluates the influence of the Azerbaijan crisis of 1945–46 on evolving perceptions of the Soviet Union within the British Foreign Office. Utilising records from the National Archives and personal papers, it synthesises the history of the Azerbaijan crisis with studies of Britain's changing Soviet policy, previously focused solely on the Northern Department and Moscow representative Frank Roberts. In so doing, the paper provides an original diplomatic history which argues that, although Europe remained the strategic priority for Foreign Secretary Ernest Bevin, Iranian developments were of greater significance in prompting a perceptual transition from cooperation to Cold War confrontation.